Effects of roasting temperature and time on the quality of cold-pressed Sacha Inchi oil from industrial practices in Thailand - Chatchawan, Chotimarkorn; Teerasak, Punvichai; Patima, Permpoonpattana; Umaporn, Pastsart (Journal of Food Technology Research, 2025)
This study aimed to determine the effects of roasting temperature (60°C and 80°C) and time (10, 20, and 30 min) on the quality, oxidative stability, and antioxidant properties of cold-pressed Sacha Inchi oil. Oil samples were evaluated for chemical composition, total phenolic content (TPC), antioxidant activity (DPPH and ABTS assays), peroxide and p-anisidine values, tocopherol and phytosterol contents, and color parameters under different roasting conditions. The results showed that moderate roasting (80°C, 20 min) significantly increased TPC and antioxidant activity (p < 0.05), while extended roasting (80°C, 30 min) led to the loss of polyunsaturated fatty acids (PUFAs), tocopherols, and increased secondary oxidation. Phytosterol levels remained stable across all treatments, indicating resistance to thermal degradation. Roasting also caused increased yellowness (b*) and decreased lightness (L*) due to the Maillard reaction and phenolic oxidation. These findings suggest that roasting at 80°C for 20 min is optimal for improving antioxidant capacity and oxidative stability while preserving the functional components. The results provide a practical approach for improving oil quality in industrial processing by optimizing roasting conditions to enhance the functional and nutritional properties of cold-pressed Sacha Inchi oil.